The Best Botanical Gardens in the World (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The article reveals the features of botanical gardens and their importance in the modern world. An analysis of such gardens and parks in different countries was carried out. In the article, the examples of botanical gardens and parks with the most interesting architectural and compositional solutions as well as architects and artists are the creators of botanical gardens are given.